A New Model for Catalyzing Translational Science: The Early Stage Investigator Mentored Research Scholar Program in HIV Vaccines. Issue 2 (30th December 2014) - Adamson, Blythe J.S.; Fuchs, Jonathan D.; Sopher, Carrie J.; Flood, Danna M.; Johnson, R. Paul; Haynes, Barton F.; Kublin, James G.; ,
Abstract: Engagement of early stage investigators (ESIs) in the search for a safe and effective vaccine is critical to the success of this highly challenging endeavor. In the wake of disappointing results from a large‐scale efficacy trial, the HIV Vaccine Trials Network (HVTN) and Center for HIV/AIDS Vaccine Immunology (CHAVI) developed a novel mentored research program focused on the translation of findings from nonhuman primate studies to human trials of experimental vaccines. From 2008 to 2011, 14 ESI Scholars were selected from 42 complete applications. Post program surveys and tracked outcomes suggest that the combination of flexible funding, transdisciplinary mentorship, and structured training and networking promoted the scientific contributions and career development of promising ESIs. Embedding a multicomponent research program within collaborative clinical trial networks and research consortia is a promising strategy to attract and retain early career investigators and catalyze important translational science.